2019
DOI: 10.2147/ott.s205688
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>Ilex hainanensis Merr</em> targets ITGAV to suppress the proliferation and metastasis of osteosarcoma cells</p>

Abstract: Background: Osteosarcoma (OS) is the most common primary malignant bone tumor. Hence, there is an urgent need to identify effective and safe therapeutic agents against OS. It has been reported that Ilex hainanensis Merr (IME) possesses antitumor properties. Integrin subunit alpha V (ITGAV) is important for the diagnosis, treatment, and prognosis of tumors. Purpose: The objective of this study was to whether IME can play a role in the treatment of osteos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Numerous evidence indicates that up-regulation of CD51 is significantly associated with cancer progression and poor prognosis in multiple types of cancers, such as gastric cancer (Wang et al, 2019), osteosarcoma (Pei et al, 2019), colorectal cancer (Flum et al, 2018), and nasopharyngeal carcinoma (Ding et al, 2017). The expressions and functions of CD51 have been shown to be dysregulated in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous evidence indicates that up-regulation of CD51 is significantly associated with cancer progression and poor prognosis in multiple types of cancers, such as gastric cancer (Wang et al, 2019), osteosarcoma (Pei et al, 2019), colorectal cancer (Flum et al, 2018), and nasopharyngeal carcinoma (Ding et al, 2017). The expressions and functions of CD51 have been shown to be dysregulated in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…OS is the most general malignant bone tumor, while an urgent need is required to identify novel effective therapeutic agents for the protection of OS [14]. Evidence has demonstrated that some certain lncRNAs, miRNAs or some certain genes could be involved in the OS growth.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ITGAV is highly expressed in osteosarcoma, hepatocellular carcinoma, and oesophageal adenocarcinoma tissues compared to normal tissues. 51 , 52 , 53 Additionally, inhibition of ITGAV has been shown to reduce tumour growth and metastasis in a variety of cancers. 54 , 55 , 56 Herein, we observed that ITGAV was highly expressed in human ESCC tissues (Figure 1A–C ) and that increased ITGAV levels were related with poor overall survival (Figure 1D ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ITGAV is highly expressed in osteosarcoma, hepatocellular carcinoma, and oesophageal adenocarcinoma tissues compared to normal tissues 51–53 . Additionally, inhibition of ITGAV has been shown to reduce tumour growth and metastasis in a variety of cancers 54–56 .…”
Section: Discussionmentioning
confidence: 99%